An investigative study on the effect of stock market participation and financial literacy in Pakistan - Osama, Muhammad (2022)
Indulgence in stock markets and financial literacy have been under debate for a very long time and several scholars have stated their opinions on this topic. This research examines the relationship between the aforementioned variables in the scope of Pakistan. To carry out this result, inspiration was taken from research done in other parts of the world because this topic is relatively less research in a developing country like Pakistan. After the relevant literature review, a questionnaire was formulated and distributed using the web to individuals of all age groups and then three models were run using Stata 14. The models included independent variables like financial literacy, age, gender, anxiety level etc. The first two models were linear regression models, and the third model was a two staged least square model. We have achieved decent results by running these models as we have found that financial literacy does impact the stock market participation if the demographic and psychological factors are considered. We have also been able to identify key trends that imply that in Pakistan, like other countries, men tend to participate more in the stock market. Overall, we believe that this research is a great step in solving the mystery of low stock market participation rate in Pakistan.